2017
DOI: 10.1038/s41598-017-16988-w
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of TSC1 and TSC2 genes in Tuberous Sclerosis Complex patients from Greece

Abstract: Tuberous sclerosis complex (TSC) is a rare autosomal dominant disorder causing benign tumors in the brain and other vital organs. The genes implicated in disease development are TSC1 and TSC2. Here, we have performed mutational analysis followed by a genotype-phenotype correlation study based on the clinical characteristics of the affected individuals. Twenty unrelated probands or families from Greece have been analyzed, of whom 13 had definite TSC, whereas another 7 had a possible TSC diagnosis. Using direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
0
24
0
7
Order By: Relevance
“…The familial cases showed no difference in the mutation frequency between TSC1 and TSC2 14,25,36 , but Dabora et al 25 pointed out that the reported frequencies of TSC1 and TSC2 mutations in familial cases could be biased by the small number of families studied. Germline mosaicism was suggested in one of the familial cases (ET28) and even though germline mosaicism is rarely seen in TSC (6%) and we found a somewhat lower rate (1/66 cases; 1.5%), a conservative 2-3% recurrence risk should be advised for apparently sporadic TSC families 41 Our search of the literature and public databases for previous reports of the 62 mutations found in TSC1/TSC2 allowed us to determine that 25 (40%) of the PV/LPV found in the present work were novel, which was a higher proportion than those found in previous studies (38%, 29%, 22%) using Greek and Malaysian populations 15,26,32 . This is expected since this disease presents high allelic and locus heterogeneity, and emphasizes the importance of implementing multiple and diverse molecular techniques to evaluate coding and non-coding regions in both genes, and to discriminate SV from CNV.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The familial cases showed no difference in the mutation frequency between TSC1 and TSC2 14,25,36 , but Dabora et al 25 pointed out that the reported frequencies of TSC1 and TSC2 mutations in familial cases could be biased by the small number of families studied. Germline mosaicism was suggested in one of the familial cases (ET28) and even though germline mosaicism is rarely seen in TSC (6%) and we found a somewhat lower rate (1/66 cases; 1.5%), a conservative 2-3% recurrence risk should be advised for apparently sporadic TSC families 41 Our search of the literature and public databases for previous reports of the 62 mutations found in TSC1/TSC2 allowed us to determine that 25 (40%) of the PV/LPV found in the present work were novel, which was a higher proportion than those found in previous studies (38%, 29%, 22%) using Greek and Malaysian populations 15,26,32 . This is expected since this disease presents high allelic and locus heterogeneity, and emphasizes the importance of implementing multiple and diverse molecular techniques to evaluate coding and non-coding regions in both genes, and to discriminate SV from CNV.…”
Section: Discussionmentioning
confidence: 65%
“…In the tuberin-binding domain (exons 10-13), in contrast, no PV was identified in our patients. There is debate as to whether this domain is a mutation region: some studies showed it to be a low-frequency mutation site 25,[31][32][33][34][35] , while others found the opposite 5,14,15,36 . In TSC2, the GTPase-activating protein (GAP) binding domain (exons 35-39) contained 10 out of the 43 total SV (23%) identified herein, and the remaining were distributed throughout the gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, intellectual disability (ID), learning disabilities, autism spectrum disorder, subependymal nodules (SENs), retinal hamartomas, and renal angiomyolipomas are seen more frequently in patients with a TSC2 pathogenic variant than in those with a TSC1 pathogenic variant, whereas cortical tubers and hypomelanotic macules are equally common in all patients (Au et al, 2007;Dabora et al, 2001;Sancak et al, 2005). These findings have been recently replicated by smaller studies on TSC cohorts from countries that had not been studied previously (Avgeris et al, 2017;Rosset et al, 2017;Yang et al, 2017), confirming that TSC manifestations do not vary with ethnicity. Moreover, a recent study by Overwater et al (2016) assessing brain pathology found that cortical tubers (more often larger and cystic), SENs (more often calcified), subependymal giant cell astrocytomas (SEGA), and radial migration lines are more likely to occur in patients with a TSC2 pathogenic variant.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 83%
“…Tuberous sclerosis complex (TSC) is a genetic disorder characterized by mutations in TSC1 (* 605284) or TSC2 (* 191092) genes (1). TSC1 gene (* 605284) encodes hamartin protein while TSC2 gene (OMIM) encodes tuberin protein (1,2). Heterozygous mutations in these two genes are found in about 75%-90% (31% of mutations are found in TSC1 gene and 69% of mutations are in TSC2 gene) according to the TSC clinical diagnostic criteria (1).…”
Section: Introductionmentioning
confidence: 99%